JENIS KELAMIN SEBAGAI MODERASI DALAM HUBUNGAN KECEMASAN SOSIAL DAN INAUTHENTIC SELF PRESENTATION PADA REMAJA PENGGUNA INSTAGRAM - Merryn Oktavia Sutarman; Agustina Agustina (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Instagram is frequently used by adolescents as a platform to present themselves and gain social recognition. Inauthentic self-presentation has become a common strategy to construct a positive self-image and avoid negative judgment. This study aims to examine the relationship between social anxiety and inauthentic self-presentation among adolescent Instagram users, as well as to investigate the moderating role of gender. A quantitative correlational method was employed with purposive sampling. The participants consisted of 200 adolescents (97 males and 103 females) who owned Instagram accounts and had uploaded personal content. The instruments used were the Social Anxiety Scale for Social Media Users (SAS-MU) and the Self-Presentation on Facebook Questionnaire (SPFBQ). The results of the correlation analysis indicated a significant positive relationship between social anxiety and inauthentic self-presentation (r = 0.353, p < 0.05). However, the moderation regression analysis revealed that gender did not moderate this relationship (B = 0.089, p = 0.199). In conclusion, higher levels of social anxiety are associated with greater tendencies toward inauthentic self-presentation among adolescents, regardless of gender. ABSTRAK Instagram kerap digunakan remaja sebagai sarana menampilkan diri untuk memperoleh pengakuan sosial. Strategi inauthentic self-presentation pun menjadi umum dalam membentuk citra diri positif dan menghindari penilaian negatif. Penelitian ini bertujuan untuk mengetahui hubungan antara kecemasan sosial dan inauthentic self-presentation pada remaja pengguna Instagram, serta menguji peran jenis kelamin sebagai variabel moderator. Penelitian ini menggunakan metode kuantitatif korelasional dengan teknik purposive sampling. Partisipan berjumlah 200 remaja (97 laki-laki dan 103 perempuan) yang memiliki akun Instagram dan pernah mengunggah konten tentang diri sendiri. Instrumen yang digunakan adalah Social Anxiety Scale for Social Media Users (SAS-MU) dan Self-Presentation on Facebook Questionnaire (SPFBQ). Hasil analisis korelasi menunjukkan adanya hubungan positif yang signifikan antara kecemasan sosial dan inauthentic self-presentation (r = 0.353, p < 0.05). Namun, hasil analisis regresi moderasi menunjukkan bahwa jenis kelamin tidak memoderasi hubungan tersebut (B = 0.089, p = 0.199). Kesimpulannya, semakin tinggi kecemasan sosial, semakin tinggi kecenderungan remaja menampilkan diri secara tidak autentik, tanpa perbedaan signifikan antara laki-laki dan perempuan.